OPENPLC HARDWARE SPEED PERFORMANCE COMPARISON - Niauronis, Saulius (PROFESSIONAL STUDIES: Theory And Practice, 2023)
Programmable Logic Controllers (PLCs) are critical components in industrial automation. As the technology behind PLCs continues to evolve, there is an ever-growing range of PLC hardware available in the market and their performance and functionality can vary significantly. Choosing the right PLC for a given application is thus a challenging task, requiring a thorough understanding of the available options and their capabilities. This approach involves running benchmarking tests on different PLCs to measure their performance and compare them. In this article, we compare the edge boundaries of time-based parameters of different PLC hardware, including open-source embedded controllers (Arduino and ESP8266) working with software such as OpenPLC and also Wago programmable logic controller PFC200